Structural Insights into Ligand-Induced Conformational Changes in Adenine Phosphoribosyl Transferase from Fusobacterium nucleatum - Kim, Bogeun; Hwang, Jisub; Do, Hackwon; Shim, Youn-Soo; Lee, Jun Hyuck (Protein and Peptide Letters, 2026)
<span class=
Keywords: crystal structure